ACUAN DAN RUANG LINGKUP EVALUASI PADA MATA PELAJARAN FIQH DI SMP ISLAM AMANAH UMMAH MOJOLABAN SUKOHARJO - Pangesti, Juni Swan; Ridho, Ahmad Rosyid; Suparman, Muh. Fatahillah (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This research aims to investigate the references and scope of evaluation in the Fiqh subject at SMP Islam Amanah Ummah Mojolaban Sukoharjo. With a deep focus, this study employs a qualitative approach involving observation, interviews, and document analysis. The main objectives are to explore the role of Islamic religious teachers in enhancing students' learning motivation and to assess the success of integrating religious values into the evaluation. The qualitative method is chosen to gain an in-depth understanding of the phenomena, with data collection through direct observation and interaction with teachers and students. The research findings indicate that the evaluation in the Fiqh subject at SMP Islam Amanah Ummah Mojolaban Sukoharjo has successfully integrated religious values. However, there is a need to enhance the variety of evaluation methods, provide additional training for teachers, and refine annual evaluation reports. Concrete recommendations are presented to improve the effectiveness of educational evaluation in the Fiqh subject.